Hubungan Hukum Para Pihak Dalam Transaksi Jual Beli Berbasis E-Commerce - Elly Kusdiana Hobaidah; Abintoro Prakoso; Sjaifurrachman Sjaifurrachman (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
This study discusses legal issues in buying and selling through e-commerce, particularly the challenges in fulfilling the valid agreement requirements, especially regarding consent. The absence of face-to-face interaction between sellers and buyers makes it difficult to determine the timing and form of legal consent. The purpose of this research is to understand the legal relationship between sellers and buyers in e-commerce transactions and to analyze legal responsibilities in case of violations or disputes. This study uses a normative legal method with a statutory approach, and data is collected through literature review of regulations, legal doctrines, previous research, journals, and relevant articles. Data analysis is conducted qualitatively by systematically reviewing and organizing the data. The results show that sales agreements through e-commerce have the same legal force as conventional agreements as long as they meet the valid agreement requirements. Consent is considered to occur when the consumer takes an affirmative action, such as clicking approval within the system. These agreements are legally valid and binding according to Article 18 Paragraph (1) of the Electronic Information and Transactions Law (UU ITE). However, if the element of consent is unclear, the agreement remains valid but may be canceled if it does not meet the subjective or objective requirements as regulated in Article 1320 of the Civil Code